(untitled) (Quinto Sol, 2018)
This paper studies the arguments regarding the regulation of freedom of the press in Corrientes during the second half of 19th century. In the first section I describe the main features of Corrientes’ newspapers and the political context in which these discussions were held. Later, I analyze the participation of Agustín Justo, Miguel Morel and Santiago Baibiene in newspapers from Entre Ríos and Buenos Aires. The links between the debates about the freedom of press and the performance of the journalists in exile shows that these controversies revolved around three issues: the moral duties attributed to the press for the consolidation of a republican system; the limitations regarding the legitimacy of political dissent, and the role of the press in the trajectories of political elites.